Problem-Focused Coping, Self-Efficacy, and Stress in Early Adults - Rachmawati Nurfadillah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The purpose of this study is to examine the effect of problem-focused coping and self- efficacy on stress that occurs in the early adult phase. The participants of this study are 101 individuals who are in the early adult phase, namely 21-40 years old who live on the island of Java. This research design is cross sectional and non-experimental research. The measuring instruments used are DASS-21 to measure stress, GSES to measure Self-efficacy, and adaptation of The Way of Coping to measure Problem-Focused Coping. The sampling technique used was purposive sampling. The results obtained in this study are the absence of the overall influence of the two variables, namely Problem-Focused Coping and Self- efficacy.